Review on the book PhD Mukhit-Ardager Sydyknazarov Uninterrupted History of Nationhood in Kazakhstan. The Kazakh State on European and American Maps of the XVI-XIX Centuries. Atlas. Brussels, 2021. 532 p - Burkutbay G. , Ayagan (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The review analyzes the unique work of the candidate of philological sciences, PhD doctor of political science, the Director of the Institute of Contemporary Studies of L.N. Gumilyov Eurasian National University Mukhit-Ardager Karzhaubayuly Sydyknazarov “Continuous statehood of Kazakhstan in the flow of history. The Kazakh state on European and American maps of the 16th-19th centuries Atlas. – Brussels, 2021. – 532 pages. The book is an Atlas from a copy of 130 geographical maps extracted by a scientist from the archives of Europe and the USA with a variety of information on the history of the process of statehood on the territory of Kazakhstan in the period from the 16th-19th centuries. The maps compiled by foreign cartographers reflected data on such issues as the place of settlement, toponymy and ethnonymy of the region, names of states and many others. The maps of European and American researchers incorporated all the known achievements of that time in collecting and systematizing data on the states that already existed at that time. Many of the maps are richly illustrated and contain a lot of useful and important information for scientists, diplomats, politicians and students. The materials of the Atlas make it possible to understand that as the Europeans moved to the east, their knowledge in onomastic of the studied territories, the way of life of the local population became more complete and reliable.